2018
DOI: 10.1137/17m1133798
|View full text |Cite
|
Sign up to set email alerts
|

The Corners of Core Partitions

Abstract: In this paper, we are concerned with counting corners of core partitions. We introduce the concepts of stitches and anti-stitches, which are pairs of cells in a quotient space which we call wrap-up space. We prove that the anti-stitches of a rational Dyck path are in bijection with the segments of structure sets of the corresponding core partition, therefore the corners of a core partition can be counted by the number of stitches or anti-stitches. Based on these results, for coprime positive integers a and b, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…, t p . Huang and Wang [11] enumerated the number of (t, t + 1)-cores, (t, t + 1, t + 2)-cores with the fixed number of corners, where these results are generalized to (t, t + 1, • • • , t + p)-cores in [4]. As far as we know, it seems new to get the formula for the number of t-core partitions with the fixed number of corners, which we enumerate this by using the path interpretation.…”
Section: Cornerless Motkzin Paths and T-coresmentioning
confidence: 99%
“…, t p . Huang and Wang [11] enumerated the number of (t, t + 1)-cores, (t, t + 1, t + 2)-cores with the fixed number of corners, where these results are generalized to (t, t + 1, • • • , t + p)-cores in [4]. As far as we know, it seems new to get the formula for the number of t-core partitions with the fixed number of corners, which we enumerate this by using the path interpretation.…”
Section: Cornerless Motkzin Paths and T-coresmentioning
confidence: 99%
“…Also, simultaneous core partitions are connected with Motzkin paths and Dyck paths (see [9,11,39,40]). Some statistics of simultaneous core partitions, such as numbers of partitions, numbers of corners, largest sizes and average sizes, have attracted much attention in the past twenty years (see [2,3,4,7,8,10,13,14,15,18,20,21,23,24,25,29,31,33,35,37,42,43,44]). For example, Anderson [3] showed that the number of (s 1 , s 2 )-core partitions is equal to 1 s 1 +s 2 s 1 +s 2 s 1…”
Section: Introductionmentioning
confidence: 99%